Haloperidol for delirium in critically ill patients – protocol for a systematic review. Issue 5 (14th February 2018) - Barbateskovic, M.; Kraus, S. R.; Collet, M. O.; Mathiesen, O.; Jakobsen, J. C.; Perner, A.; Wetterslev, J.
Abstract : Background: In the intensive care unit, the prevalence of delirium is high. Delirium has been associated with morbidity and mortality including more ventilator days, longer intensive care unit stay, increased long‐term mortality, and cognitive impairment. Thus, the burden of delirium for patients, relatives, and societies is considerable. The objective of this systematic review was to critically access the evidence of randomised clinical trials on the effects of haloperidol vs. placebo or any other agents for delirium in critically ill patients. Methods: We will search for randomised clinical trials in the following databases: Cochrane Library, MEDLINE, EMBASE, Science Citation Index, BIOSIS, Cumulative Index to Nursing and Allied Health Literature, Latin American and Caribbean Health Sciences Literature, and Allied and Complementary Medicine Database. Two authors will independently screen and select references for inclusion using Covidence, extract data and assess the methodological quality of the included randomised clinical trials using the Cochrane risk of bias tool. Any disagreement will be resolved by consensus. We will analyse the extracted data using Review Manager, STATA 15, and Trial Sequential. Analysis: The aim of this study was to assess the quality of the evidence, we will create a 'Summary of Findings' table containing our primary and secondary outcomes using the GRADE assessment. Discussion: Our ambition with this systematic review is to provide reliable and powered evidence to better inform decision makers on the use of or future trials with haloperidol for the management of delirium in critically ill patients.